2007
DOI: 10.1002/jcp.21027
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin‐mediated hepatocellular carcinoma cell migration: Cooperative action via proteinase‐activated receptors 1 and 4

Abstract: Proteinase-activated receptor-1 (PAR(1)), a thrombin receptor and the prototype of a newly discovered G-protein-coupled receptor subfamily, plays an important role in tumor development and progression. In this study, we documented the expression of the thrombin receptors PAR(1), PAR(3), and PAR(4) in permanent hepatocellular carcinoma (HCC) cell lines and primary HCC cell cultures. Stimulation of HCC cells with thrombin and the PAR(1)-selective activating peptide, TFLLRN-NH(2), increased transmembrane migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 46 publications
1
53
0
1
Order By: Relevance
“…Positive expression of PAR4 in some tumors have been found in previous studies and is thought to be involved in hepatocellular carcinoma cell migration and colon cancer progression (Kaufmann et al, 2007;Gratio et al, 2009). It was also reported that PAR4 activation contributed to the hematogenous metastasis of melanoma using the knockout mice (Camerer et al, 2004).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Positive expression of PAR4 in some tumors have been found in previous studies and is thought to be involved in hepatocellular carcinoma cell migration and colon cancer progression (Kaufmann et al, 2007;Gratio et al, 2009). It was also reported that PAR4 activation contributed to the hematogenous metastasis of melanoma using the knockout mice (Camerer et al, 2004).…”
Section: Discussionmentioning
confidence: 72%
“…For instance, Primary hepatic cell cancer (HCC) was reported to be negative in one study (Rullier et al, 2006). While another reported a 100% positivity on 2 primary HCC cells and two cancer cell lines (Kaufmann et al, 2007). RT-PCR revealed no PAR4 mRNA in the LnCaP prostate cell line and MDA-MB-231 breast cell line while by FACS analysis they were shown to be positive (Elste et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLA2 is known to be involved in hepatic stellate cell activation (19) and is critically implicated in thrombininduced signalling in different cell types including platelets (20,21) and endothelial cells (22)(23)(24). In addition, from recently published data, a role for thrombin in liver fibrosis and hepatocellular carcinoma progression has been suggested (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a role for the thrombin-PAR 1/4 -triggered signaling in HCC progression has been suggested (28). In this context, it is important to note that hepatocellular carcinoma (HCC) belongs to the 'coagulation type' tumors, in which there is an important role for thrombin formation within the tumor microenvironment (29,30).…”
Section: Introductionmentioning
confidence: 99%